2020
DOI: 10.1109/access.2020.3019794
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Volt–Var Curve Setting of a Smart Inverter for Improving Its Performance in a Distribution System

Abstract: We propose an algorithm to set the parameters of volt-var curves to improve the performance of distributed generation. Specifically, we optimally set the volt-var curves of the smart inverter for proper control of the distributed generation output. To improve the overall distribution system performance, we consider the minimization of voltage deviation, system loss, and peak of reactive power in an objective function, thereby providing optimal volt-var curve parameters. The proposed algorithm overcomes various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The reactive power control range of DG is determined by the inverter capacity of DG and the power factor limit magnitude. Regardless of the active power, the reactive power can be controlled independently within the setting range, and active power control of DG is impossible [31]. In addition, in this paper, the reactive power control variables of DG are divided according to sections.…”
Section: ) Inverter Of Dg Constraintsmentioning
confidence: 99%
“…The reactive power control range of DG is determined by the inverter capacity of DG and the power factor limit magnitude. Regardless of the active power, the reactive power can be controlled independently within the setting range, and active power control of DG is impossible [31]. In addition, in this paper, the reactive power control variables of DG are divided according to sections.…”
Section: ) Inverter Of Dg Constraintsmentioning
confidence: 99%
“…360 candidate patterns are defined by the central voltage V ref , dead zone, and slope, and cover almost all the volt-var curves that may be applied in practice. As another solution, the volt-var curve can be determined by solving the volt-var curve optimization problem [24][25][26][27], which is one of state-of-the-art counterparts to determine the volt-var curve. However, the solution obtained should be equal to or very close to one of the 360 patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The specification of the volt-var curve has been discussed as an evaluation index for the hosting capacity of PV generation based on the computer simulation using actual distribution lines in California [23]. An optimization method based on a genetic algorithm has been proposed to optimize the setting of the volt-var function, and it was shown that the control characteristics of the distribution system can be improved [24][25][26]. A method to determine the volt-var curve based on the relationship between the optimum reactive power and the inverter voltage using the interior point method has been proposed [27].…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…The current state of art optimizes the volt-var curves over a long time horizon, but the optimization is not able to address the temporal dynamics in a minutes time frame [22]. Additionally, the state-of-the-art approaches are based on central optimization [23], which limits the applicability of such a method [24] in many practical systems. The proposed enhances the flexibility of operation by considering the spatial and temporal dynamics of the distribution system and optimizing the system in a granular, distributed manner.…”
Section: Contributionsmentioning
confidence: 99%